EXCLUDED RESTRICTIONS IN VERTICAL AGREEMENTS IN COMPETITION LAW - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Excluded restrictions are regulated by Art. 5 of Commission Regulation on the application of Article 101(3) of the Treaty on the Functioning of the European Union to categories of vertical agreements and concerted practices. Excluded restrictions in vertical agreements represent special type of vertical restraints that, if contained in an agreement, cannot be exempted from prohibition of restrictive agreements. We can speak of an excluded restriction if the vertical agreement contains a non-compete obligation for which the Regulation stipulates that it cannot benefit from the block exemption. The subject of analysis in this paper is the legal regulation of excluded restrictions in EU competition law. Given that excluded restrictions involve the existence of a non-compete obligation, the paper also examines the concept of the non-compete obligation and its various forms.